2018
DOI: 10.1021/acs.nanolett.8b03503
|View full text |Cite
|
Sign up to set email alerts
|

Diradical Character as a Guiding Principle for the Insightful Design of Molecular Nanowires with an Increasing Conductance with Length

Abstract: In recent years, a considerable interest has grown in the design of molecular nanowires with an increasing conductance with length. The development of such nanowires is highly desirable because they could play an important role in future molecular-scale circuitry. Whereas the first experimental observation of this nonclassical behavior still has to be realized, a growing number of candidate wires have been proposed theoretically. In this Letter, we point out that all the wires with an anti-Ohmic increasing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 57 publications
4
91
0
Order By: Relevance
“…On the contrary, the electric perturbation favors polarized quinoidlike resonance forms in pP, provoking a decrease of the aromatic stabilization. Stuyver et al 12,27,28 further explained the extraordinary conductance shown by the pX2 chains in terms of an increasing diradical character with the chain length, which comes along with the formation of aromatic resonance forms.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the electric perturbation favors polarized quinoidlike resonance forms in pP, provoking a decrease of the aromatic stabilization. Stuyver et al 12,27,28 further explained the extraordinary conductance shown by the pX2 chains in terms of an increasing diradical character with the chain length, which comes along with the formation of aromatic resonance forms.…”
Section: Introductionmentioning
confidence: 99%
“…The (2,2) space is a good choice for the largest systems, where the HOMO and LUMO are far from the remaining virtual and occupied orbitals. Also, for smaller systems, the choice of a (14,14) active space is accurate enough according to previous studies. 14 These calculations show that the ground state of the naphthalene-based structures is mainly represented by the doubly occupied HOMO configuration.…”
mentioning
confidence: 99%
“…Figure S1. As suggested by Stuyver et al, 111 increase in diradical character is intimately related with high transmission. Triyne-SMe is still able to retain its closed-shell electron structure at 90°, and therefore has no effect like this.…”
Section: Even-n Cumulenic Carbon Wiresmentioning
confidence: 63%